The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1139/apnm-2018-0376
|View full text |Cite
|
Sign up to set email alerts
|

Neither repetition duration nor number of muscle actions affect strength increases, body composition, muscle size, or fasted blood glucose in trained males and females

Abstract: A key variable within resistance training (RT) is that of repetition duration; the time (seconds; s) taken to perform the concentric and eccentric muscle actions of a repetition. Research has produced equivocal results with regards to strength and muscle mass increases whilst many studies have created parity in the number of repetitions though there has been a disparity in load used and time-under-load (TUL). The purpose of this study was to compare load, and TUL matched groups performing resistance exercise u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 52 publications
0
10
0
1
Order By: Relevance
“…On the other hand, some authors have investigated the effects of both CON and ECC in maximal dynamic strength. Pereira et al (48) and Pearson et al (47) found that the use of 4/0/1/0 and 3/0/1/0, respectively, induce greater improvements (+18-24%) than in the 1/0/1/0 control group, which is supported by studies developed by Carlson et al (4), Mike et al (43), and Neils et al (45). Therefore, the use of fast CON MAD with medium ECC MAD (3-4/0/1/0) could be a suitable strategy to be considered with trained subjects to retain elastic energy in the ECC to transfer it to the subsequent CON (39,42).…”
Section: Discussionmentioning
confidence: 74%
“…On the other hand, some authors have investigated the effects of both CON and ECC in maximal dynamic strength. Pereira et al (48) and Pearson et al (47) found that the use of 4/0/1/0 and 3/0/1/0, respectively, induce greater improvements (+18-24%) than in the 1/0/1/0 control group, which is supported by studies developed by Carlson et al (4), Mike et al (43), and Neils et al (45). Therefore, the use of fast CON MAD with medium ECC MAD (3-4/0/1/0) could be a suitable strategy to be considered with trained subjects to retain elastic energy in the ECC to transfer it to the subsequent CON (39,42).…”
Section: Discussionmentioning
confidence: 74%
“…A second subgroup analysis was conducted to determine whether age influenced strength adaptations due to resistance training velocity. The number of effect sizes included in the young group was 20 from 19 studies (7,9,22,27,31,32,34,36,40,45,46,48,49,51,53,66,67,71,80), whereas 5 studies were included in the older group (6,17,39,44,75). Test of moderators found no significant subgroup effect between age groups, indicating no significant difference between subgroups (QM 5 0.09, p 5 0.77).…”
Section: Meta-analysis Resultsmentioning
confidence: 99%
“…La evidencia actual (Carlson et al, 2018;Chaves et al, 2020;Shibata et al, 2018;Pereira et al, 2016) sugiere que un tiempo óptimo para obtener adaptaciones hipertróficas estaría en un rango de…”
Section: Conclusionesunclassified